A- Level Textile Technology and Design Curriculum Compatibility with Industry Requirements in Harare, Zimbabwe - Lois Ranganai Mberengwa; Audrey Chirapa (African Journals on line (AJOL), 2023)
Through descriptive design, this study ought to establish the compatibility of the A-level Textile Technology and Design (TTD) curriculum with the industry requirements in Harare, Zimbabwe. The study employed both quantitative and qualitative techniques through a questionnaire and interview schedule. The population comprised of 120 A-level learners and five teachers from five schools as well as eight factory managers. Forty learners who had studied the subject for at least one year and teachers based on their experience in teaching were purposely selected to constitute the sample. Three factory managers from clothing industries in Harare City were conveniently selected based on their willingness to participate in the study. Data was treated through descriptive statistics and thematically. The study established that learners did not acquire adequate essential concept in designing, pattern making, computer aided designing, use of industrial sewing equipment and business enterprise which are critical for business or employment in the clothing industry. Some study area were found to be compatible with the requirements of the clothing industry and entrepreneurship, but the content was not well taught. Teachers were not proficient with new skills and knowledge in the updated syllabus. The majority of the learners was either neutral, disagreed or strongly disagreed to have acquired the intermediate skills related to the updated Textile Technology and Design Curriculum. Therefore, a more skills based curriculum is recommended. In-service training of TTD teachers in business and entrepreneurship skills is also recommended.